PEMBINAAN KARAKTER PEDULI LINGKUNGAN SEBAGAI UPAYA MEMPEROLEH ADIWIYATA MANDIRI DI SMA NEGERI 1 JATILAWANG KABUPATEN BANYUMAS (Civic Education Program, Universitas Negeri Semarang, 2022)
This research is motivated by the award that has been obtained by SMA Negeri 1 Jatilawang as one of the schools in Banyumas Regency which has received the Adiwiyata award at the Regency/City level to the Adiwiyata award at the National level and is now trying to get the Adiwiyata award at the Mandiri level. The results showed that SMA Negeri 1 Jatilawang carried out environmental care character building activities as an effort to obtain independent adiwiyata. Environmental care character building activities consist of: 1. Activities carried out in learning by inserting material about the environment in each subject using an integrated method in the subject. Activities outside of learning such as students are invited directly in the process of caring for plants using habituation or self-development methods. Activities through the teacher's exemplary method provide examples for students to behave in caring for the environment. Through the method of advice in the form of the teacher giving advice to students in the context of character building, then the reward and punishment method in the form of giving gifts to students so that they are motivated and giving punishment in the form of giving sanctions to students who behave not caring about the environment. The obstacles faced in fostering environmental care characters include students' concern for the environment and students' enthusiasm in carrying out environmental care character building.